Efektivitas Pemberian Betahistin pada Pasien Vertigo Usia 53 Tahun - Muhammad Gilang Ramadhan; Moh. Reza Zainal Abidin; Emy Wardani (Jurnal Syntax Admiration, 2024)
The lifestyle applied in today's society has a considerable impact on disease shifts. One of the diseases that is often the reason someone goes to the hospital is vertigo. Based on a case report, we found a 53-year-old patient with complaints of spinning dizziness that was felt when he woke up or when his head changed position two weeks ago. Based on a guided history and physical examination, the patient was diagnosed with vertigo. So the doctor gave the main treatment, namely betahistine (6 mg, given as 1 tablet three times a day). The use of betahistine has been shown to significantly reduce the number of attacks per month in vertigo patients. Betahistine is effectively used in the treatment of vertigo because it can reduce the frequency, severity, and duration of vertigo and related neurovegetative symptoms.